Benchmarking Unemployment Benefits in the EU - Klara Stovicek; Alessandro Turrini (Institute for the Study of Labor (IZA), 2012)
This paper proposes a methodology for benchmarking unemployment benefits systems, with a view to assess reform needs and priorities. The methodology permits to assess different dimensions of unemployment benefit systems and to consider alternative relevant benchmarks. Looking at all relevant dimensions allows to better gauge how unemployment benefit systems perform in terms of their multi-faceted objectives (such as income support and stabilisation, incentives to take up work) and to have a more thorough assessment of each objective. Comparisons with alternative benchmarks offer the possibility of assessing against more meaningful country comparators, which take into account similarities in terms of economic fundamentals, institutions and policy settings. The methodology is applied to EU countries and results are discussed.
Keywords: J65; J68; H20; H53; 330; unemployment insurance; unemployment assistance; tax and benefit policies; benchmarking; flexicurity; Arbeitslosenversicherung; Benchmarking; Flexicurity; EU-Staaten